Factors Affecting Teenage Addiction to Games: A Literatur Review - Agus Ari Pratama; Made Yos Kresnayana; I Made Sundayana (Jurnal Ilmu Keperawatan Jiwa, 2021)
Game addiction experienced in adolescence can affect the social aspects of adolescents in living their daily lives, because of the amount of time spent in the game world. The purpose of reviewing and analyzing these articles is to classify in a simple way the factors affecting teenage addiction to games. The data collection process was carried out by filtering from 4,290 literature sources using accredited journal sites such as Ebsco and Pubmed then filtered into 30 literatures and articles relevant to this literature review as many as 8 journals based on criteria determined by the authors of each journal taken using the PRISMA diagram and starting from 2018 to 2020. The results of the article review are found that teenagers who are addicted to games affect the way they behave and in interpersonal communication. Teenagers spend more time playing games which then causes a reduced opportunity for a teenager to be involved in social interactions, so that it has a negative impact on their social life such as closing themselves off and not hanging out with many people which makes them anti-social. It is difficult for a teenager to express the emotional state they have, they prefer games as an escape when they have problems.